2019
DOI: 10.1080/00324728.2019.1683219
|View full text |Cite
|
Sign up to set email alerts
|

Over-coverage in population registers leads to bias in demographic estimates

Abstract: Estimating the number of individuals living in a country is an essential task for demographers. This study assesses the potential bias in estimating the size of different migrant populations due to over-coverage in population registers. Over-coverage-individuals registered but not living in a country-is an increasingly pressing phenomenon; however, there is no common understanding of how to deal with over-coverage in demographic research. This study examines different approaches to and improvements in over-cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 20 publications
1
40
1
2
Order By: Relevance
“…However, large differences exist between groups, with higher unregistered emigrations in groups born outside Europe. In general, unregistered emigrations follow the same patterns as the registered ones, which means that in groups in which emigrations are high, they are probably even higher than recorded (Monti, Drefahl, Mussino, & Härkönen, ).…”
Section: Methodsmentioning
confidence: 71%
“…However, large differences exist between groups, with higher unregistered emigrations in groups born outside Europe. In general, unregistered emigrations follow the same patterns as the registered ones, which means that in groups in which emigrations are high, they are probably even higher than recorded (Monti, Drefahl, Mussino, & Härkönen, ).…”
Section: Methodsmentioning
confidence: 71%
“…This permits a thorough and detailed examination of how migrant mortality varies by age, including by country of birth. Moreover, we are able to build on existing research on over-coverage in Sweden, as several approaches for adjusting for over-coverage are already available (Weitoft et al 1999;Aradhya et al 2017;Monti et al 2019). The value of our work is found in the ability to contribute to ongoing debate on what causes the migrant mortality advantage and whether empirically observed mortality differences are real or merely an artefact.…”
Section: Introductionmentioning
confidence: 99%
“…These concerns about data artefacts become even more pertinent in light of recent research on the principal source of data artefacts in mortality differentials between foreign-and native-born populations: over-coverage (Monti et al 2019). On testing three approaches for correcting for this problem in Sweden, Monti et al (2019) found the largest levels of over-coverage (i.e. the greatest number of individuals considered to have left and no longer be living in Sweden)-and therefore the largest bias in core demographic estimates among immigrants-at peak migration ages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper sheds light on these hypotheses by providing estimates of the total fertility rates (TFRs) of migrants from low-fertility countries in a moderate-fertility country. In addition to duration of stay, it also discusses other key aspects that can affect migrants' fertility: reason for migration, age at migration, return migration, and fertility before migration (e.g., Toulemon 2004;Mussino et al 2012;Monti et al 2019).…”
Section: Introductionmentioning
confidence: 99%